Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Test: 13

Answer

{$-3 - 2i\sqrt 3,-3 + 2i\sqrt 3$}

Work Step by Step

Step 1: Comparing $x^{2}+6x+21=0$ to the standard form of a quadratic equation, $ax^{2}+bx+c=0$, we find: $a=1$, $b=6$ and $c=21$ Step 2: The quadratic formula is: $x=\frac{-b \pm \sqrt {b^{2}-4ac}}{2a}$ Step 3: Substituting the values of a, b and c in the formula: $x=\frac{-(6) \pm \sqrt {(6)^{2}-4(1)(21)}}{2(1)}$ Step 4: $x=\frac{-6 \pm \sqrt {36-84}}{2}$ Step 5: $x=\frac{-6 \pm \sqrt {-48}}{2}$ Step 6: $x=\frac{-6 \pm \sqrt {-1\times16\times3}}{2}$ Step 7: $x=\frac{-6 \pm (\sqrt {-1}\times\sqrt {16}\times\sqrt 3)}{2}$ Step 8: $x=\frac{-6 \pm (i\times 4\times\sqrt 3)}{2}$ Step 9: $x=\frac{-6 \pm 4i\sqrt 3}{2}$ Step 10: $x=\frac{2(-3 \pm 2i\sqrt 3)}{2}$ Step 11: $x=-3 \pm 2i\sqrt 3$ Step 12: $x=-3 - 2i\sqrt 3$ or $x=-3 + 2i\sqrt 3$ Step 13: Therefore, the solution set is {$-3 - 2i\sqrt 3,-3 + 2i\sqrt 3$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.